Incidental Fetal Ultrasound Findings: Interpretation and Management. (15th May 2018) - Kaplan, Rebekah; Adams, Sharon
Abstract: Ultrasonography is a common component of prenatal care worldwide and is often used in early pregnancy to determine gestational age, number of fetuses, fetal cardiac activity, and placental location. Patients and their families may also consider ultrasonography a social event, as it provides confirmation and reassurance of a normal pregnancy. Ultrasound screening is typically scheduled in the second trimester to visualize fetal anatomy and confirm gestational age. Most ultrasound examinations are reassuring, but some incidentally identify structural anomalies and soft markers for aneuploidy, making it necessary for health care providers to correctly interpret these findings. The health care provider's ability to prepare patients prior to the ultrasound and deliver the necessary information needed to make informed decisions regarding any follow‐up screening or diagnostic testing is critical to reducing parental anxiety. Preparation for the anatomic survey should include counseling for normal and abnormal findings. The ethical concepts of patient autonomy and shared decision making are used as a guide in providing this critical information and enabling informed choices during follow‐up for incidental ultrasound findings.